2011
DOI: 10.3109/02770903.2011.561513
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Features of Asthma in Children Differ with Regard to the Intensity of Distal Gastroesophageal Acid Reflux

Abstract: There are differences in clinical features of asthma in children with regard to the intensity of esophageal acid exposure. Symptoms of asthma in nonatopic individuals with early onset and difficult-to-control nighttime asthma attacks suggest the possibility of concomitant, clinically relevant GER.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Children with difficult-to-treat asthma and GERD made up to 49% of the studied patient group. Kwiecien et al 2011 found that the intensity of GER was significantly correlated with severity and the difficulty-to-control asthma attacks in asthmatic children [20]. Their finding can explain the high prevalence of GERD in the current study.…”
Section: Discussionmentioning
confidence: 51%
“…Children with difficult-to-treat asthma and GERD made up to 49% of the studied patient group. Kwiecien et al 2011 found that the intensity of GER was significantly correlated with severity and the difficulty-to-control asthma attacks in asthmatic children [20]. Their finding can explain the high prevalence of GERD in the current study.…”
Section: Discussionmentioning
confidence: 51%
“…In adults with poor asthma control, abnormal distal or proximal esophageal pH was associated with oral steroid use, and proximal reflux was associated with worse quality of life, but neither was associated with FEV 1 , asthma control, or methacholine challenge (38). By contrast, Kwiecien et al noted that in 66 children with asthma with a mean age 10 years, night asthma symptoms were associated with a longer time spent at night with an esophageal pH below 4 (39). …”
Section: Gerd and Asthmamentioning
confidence: 99%
“…However, in spite of the reported association between the two clinical entities, this does not imply causality, and an important controversy still persists regarding this topic. For example, the presence of GERD does not seem to have a significant impact on pulmonary function parameters, and recent studies recognise little to no significant clinical improvement after PPI therapy in bronchial asthma patients with concomitant GERD [ 22 , 23 , 24 ].…”
Section: Pepsin Detection In Bronchial Asthmamentioning
confidence: 99%